First experience with the abdominal aortic and junctional tourniquet in prehospital traumatic cardiac arrest. (November 2020) - Balian, Fay; Garner, Alan A.; Weatherall, Andrew; Lee, Anna
Abstract: Introduction: The Abdominal Aortic and Junctional Tourniquet (AAJT) increased systemic vascular resistance, mean arterial pressure, carotid blood flow and rate of return of spontaneous circulation (ROSC) in animals with hypovolaemic traumatic cardiac arrest (TCA). The objective of this study was to report the first experience of the use of the AAJT as part of a pre-hospital TCA algorithm. Methods: This is a descriptive case series of the use of the AAJT in patients with TCA in a civilian physician-led pre-hospital trauma service in Sydney, Australia between June 2015 to August 2019. Cases were identified and data sourced from routinely collected data sets within the retrieval service. Results: During the study, 44 TCAs were attended, 22 with AAJT application. Mean time (standard deviation) to AAJT application since last signs of life was 16 (9) min. Eighteen (16 males, 2 females) patients, with median age (interquartile range) of 40 (25–58) years, were included for analysis. Seventeen patients (94%) had blunt trauma. Sixteen patients (89%) were in TCA at the time of service contact, 11 (61%) had a change in electrical activity, 4 (22%) had ROSC, and of the 6 with documented end-tidal carbon dioxide, the mean rise was 24.0 mmHg (95% CI 12.6−35.4) (P = 0.003). Three patients (17%) had sustained ROSC on arrival to the Emergency Department. No patients survived to hospital discharge. Conclusion: Physiological changes were demonstrated but there were no survivors. Further research focusing on faster application times may be associated with improved outcomes.